1997
DOI: 10.2307/3579340
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Tumor Oxygenation: A Comparison between Polarographic Needle Electrodes and a Time-Resolved Luminescence-Based Optical Sensor

Abstract: A novel oxygen sensor which does not rely on electrochemical reduction has been used to measure the oxygenation of the murine sarcoma F in a comparative study with an existing polarographic electrode that is available commercially. The prototype luminescence sensor yielded an oxygen distribution comparable with readings made using a pO2 histograph. The percentage of regions detected that had a pO2 less than 5 mm Hg was 79 and 75 using the Eppendorf pO2 histograph and the luminescence fiber optic sensor, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 13 publications
(4 reference statements)
0
47
0
Order By: Relevance
“…Hypoxia in human tumors has been estimated indirectly by measuring tumor vascularization (e.g., intercapillary distance, vascular density; West et al, 2001); the degree of DNA damage after radiation (Partridge et al, 2001); the expression of hypoxia-regulated genes (Airley et al, 2001(Airley et al, , 2003; and by hypoxia marker techniques (misonidazole; Chapman et al, 1983;pimonidazole: Arteel et al, 1995; the 2-nitroimidazole drug EF5; Evans et al, 2001). Direct measurements of tissue oxygen partial pressure (pO 2 ) have been obtained by utilizing oxygen sensitive polarographic electrodes (Eppendorf, Hamburg, Germany; e.g., Vaupel et al, 1991) and luminescence-based optical sensors (Collingridge et al, 1997). Using oxygen electrodes, it has been observed that the majority of solid tumors present median pO 2 levels lower than their normal tissue of origin.…”
mentioning
confidence: 99%
“…Hypoxia in human tumors has been estimated indirectly by measuring tumor vascularization (e.g., intercapillary distance, vascular density; West et al, 2001); the degree of DNA damage after radiation (Partridge et al, 2001); the expression of hypoxia-regulated genes (Airley et al, 2001(Airley et al, , 2003; and by hypoxia marker techniques (misonidazole; Chapman et al, 1983;pimonidazole: Arteel et al, 1995; the 2-nitroimidazole drug EF5; Evans et al, 2001). Direct measurements of tissue oxygen partial pressure (pO 2 ) have been obtained by utilizing oxygen sensitive polarographic electrodes (Eppendorf, Hamburg, Germany; e.g., Vaupel et al, 1991) and luminescence-based optical sensors (Collingridge et al, 1997). Using oxygen electrodes, it has been observed that the majority of solid tumors present median pO 2 levels lower than their normal tissue of origin.…”
mentioning
confidence: 99%
“…2 The OxyLite allows pO 2 measurement that is based on the oxygen-quenched lifetime of a luminescent ruthenium dye. 18,19 This system was used for simultaneously and continuously monitoring local tissue oxygenation and temperature at the same location, before, during and after treatment. FSaII tumors were monitored with both techniques and for all treatments, whereas LLc tumors were studied with EPR oximetry alone for the treatments that induce endogenous production of NO (insulin and electrical stimulation) on control and eNOS ÏȘ/ÏȘ mice.…”
Section: Po 2 Measurementsmentioning
confidence: 99%
“…Oxygenation in the established tumour models was measured using the OxyLite pO 2 system (Oxford Optronix Ltd, Oxford, UK) (Young et al, 1996;Collingridge et al, 1997;Seddon et al, 2001). The OxyLite probes measure pO 2 by using a fluorescence quenching technique (Young et al, 1996).…”
Section: Direct Measurement Of Pomentioning
confidence: 99%